Mülkiye Congress on International Relations - MENGÜASLAN, Hikmet (Turkish Economic Review, 2017)
Abstract. The year 2017 welcomed the first of the Mülkiye Congress on International Relations. It was titled as “The 100th Anniversary of the October Revolution: The Soviet Union, the Cold War and the International System” and held on 16-17 October in Ankara. The Congress was organized by Faculty of Political Science, Department of International Relations in Ankara University and hosted many participants from various countries and disciplines. Keywords. Mülkiye congress, International relations, Hegemony, Prague spring, Soviet Union. JEL. A14, B10, E15.